2011
DOI: 10.1080/08929092.2011.618365
|View full text |Cite
|
Sign up to set email alerts
|

Digital Drama—Toolkits, Dilemmas, and Preferences

Abstract: Artists and educators who work with young people are often under pressure to consider ways to embrace the use of digital technologies in their practice and classrooms. Drama educators are faced with a number of opportunities and dilemmas as they move to adopt a greater technology focus. This article will outline some findings from international research about young people and ICT use, and specific considerations for creating drama using digital media and online spaces. It also outlines an example of a school b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 12 publications
0
24
0
1
Order By: Relevance
“…We had a student, for instance, who was not willing to act out in front of the cameras but was always excited to be the cameraman or direct scenes. Also, to reinforce the problematic assumption that children and young people are 'digital natives' (Davis, 2011), we found that the participants in our project needed time to familiarise themselves with the digital equipment and the process. Teachers embarking on such projects need to know in advance that…”
Section: Digital Mediamentioning
confidence: 74%
See 2 more Smart Citations
“…We had a student, for instance, who was not willing to act out in front of the cameras but was always excited to be the cameraman or direct scenes. Also, to reinforce the problematic assumption that children and young people are 'digital natives' (Davis, 2011), we found that the participants in our project needed time to familiarise themselves with the digital equipment and the process. Teachers embarking on such projects need to know in advance that…”
Section: Digital Mediamentioning
confidence: 74%
“…As it was the means to create a complete piece of work to be presented to families, friends and the rest of the school, it was a great way to celebrate Greek language learning with them. As Boyd explains, the framing of the experience and the potential for an audience to receive our work heightens experience and provides a sense of being in the world (as cited in: Davis, 2011). During the festival, students had to go on stage and say a few words regarding their storytelling piece, before its Þ lming, and receive an honorary plaque for their entry to the festival to take back with them to their school.…”
Section: Digital Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…In analysing the data the range of technological tools and platforms that teachers identified using were identified. These were then clustered into the types of tools people used drawing upon previous work by one of the authors that identified that the different kinds of technologies used in the drama classroom and associated 'toolkits' (Davis, 2011). These digital tools are clustered in Table 2 as:…”
Section: Shifts To 'Online' Learning and Changes To Tool Usementioning
confidence: 99%
“…There is also more to experiment with in the IC format: use of devices could become part of the story as well as a means of recording it, and there may well be room for more explicit reflection on the best ways of using such devices or communicative practices, or to intergrate opportunities to converse at a distance in real time. As S. Davis (2011Davis ( , 2012 highlights, it cannot be assumed that learners will have (or intuitively "pick up") the skills required to use digital technologies, but neither should it be assumed that the teaching of skills necessarily provides powerful opportunities for effective learning. Further research focused on creative pedagogies and the role of digital tools is critical if we are to respond to the needs of children in the 21 st century.…”
Section: Conclusion: "Appropriateness" In Participatory Theatrementioning
confidence: 99%